PERANCANGAN SISTEM INFORMASI PERPUSTAKAAN SMP N 1 KUBUNG BERBASIS WEBSITE - Lusi Mirnawati; Reti Handayani; Edwin Anwar; Jeprimansyah, Jeprimansyah (Yayasan Nusantara Hasana Berdikari, 2025)
SMP N 1 Kubung has a library room where the current book lending system is still manual, so the process of registering, borrowing and returning books is still done in writing in a ledger and data processing will take a long time, less secure so that it will hamper the process of data processing and providing information to students. Therefore, a system is needed that can help library managers. The system is built on a website with the PHP and MySQL programming languages ​​and is useful for overcoming the difficulties of library managers in managing the available book collections. In developing the library information system at SMP N 1 KUBUNG, the SDLC method is used, this application is created using PHPMyAdmin for the database and the Visual Studio Code application as a tool for creating the information system. This website helps the recording process by automating borrowing, returning, and helping speed up the process of making the report.